Human iPSC-derived NK cells armed with CCL19, CCR2B, high-affinity CD16, IL-15, and NKG2D complex enhance anti-solid tumor activity - Yuma Fukutani; Kenji Kurachi; Yu-suke Torisawa; Kotoko Miyata; Makoto Hayashi; Kaoru Sasaki; Kodai Saitoh; Sono Watanabe; Yudai Hasegawa; Yoichi Naritomi; Yuka Igarashi; Kumiko Goto; et al. (Stem Cell Research & Therapy)
Abstract Background Studies of chimeric antigen receptor (CAR)-T and -Natural killer (NK) cells have shown promising results in treating hematological malignancies. However, there are still obstacles to effectively treating solid tumors. These include the challenges of CAR-T cell homing and infiltration, the presence of immunosuppressive microenvironments, and the potential for antigen escape in solid tumors. To overcome the known limitations of immune cell therapy, we engineered human induced pluripotent stem cell (hiPSC)-derived NK cells armed with CCL19, CCR2B, high-affinity CD16, IL-15, and NKG2D-DAP10 complex. Methods We introduced the six genes, CCL19, CCR2B, FCGR3A (CD16), IL-15, KLRK1 (NKG2D), and HCST (DAP10), which were controlled under human EF1a promoter, into hiPSCs using the piggyBac system and differentiated them into NK cells. We evaluate the antitumor function, including killing activity, antibody-dependent cytotoxicity, migration ability, and recruitment of dendritic cells. In addition, in vivo antitumor activity was determined by using an orthotopic lung cancer mouse model. Results The gene-engineered hiPSCs expressed all six transgenes, showed normal karyotypes, and were able to differentiate into CD56+ NK cells. The gene-engineered hiPSC-derived NK (eNK) cells showed improvement in viability without additional cytokine supplement in vitro and in vivo. Overexpression of NKG2D complex and high-affinity CD16 enhanced the antitumor function of the eNK cells. Forced expression of CCR2B enhanced eNK cell tumor infiltration. Forced expression of CCL19 endowed the eNK cells with the ability to recruit dendritic cells. We found that the eNK cells were able to lyse HLA-E-expressing tumor cells, but not normal human cells. Moreover, eNK cells demonstrated superior anti-tumor activity in an orthotropic lung cancer mouse model. Conclusion These proof-of-concept studies demonstrate the promise of our eNK cells as a novel adoptive cell therapy product for the treatment of solid tumors. Graphical abstract